NeuroDynamix II concepts of neurophysiology illustrated by computer simulations - Friesen, W. Otto, 1942-; Friesen, Jonathon A., 1973- (New York ; Oxford : Oxford University Press, 2010)
This text, together with its associated computer simulation lessons, teaches students about neurophysiological concepts, and then the online software further expands their knowledge through modelling experiments.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Action potentials (Electrophysiology) -- Computer simulation; Neural conduction -- Computer simulation; Neurons -- Computer simulation